Knowledge and attitude toward postoperative antithrombotic management and prevention in patients with coronary revascularization: a cross-sectional study - Liu, Chunlu; Zhang, Haijun; Yang, Liming; Chen, Lihua; Zu, Changhao; Wang, Fangfang; Dai, Yunjia; Zhao, Haiyan (Frontiers in Cardiovascular Medicine, 2024)
Background: This study aimed to explore the knowledge and attitude (KA) toward postoperative antithrombotic management and prevention among coronary artery disease (CAD) patients who underwent coronary revascularization. Methods: This cross-sectional study enrolled CAD outpatients and inpatients between May and December 2023 at Kailuan Medical Group at Tangshan. Basic demographic characteristics and KA scores were collected through a self-made questionnaire. Results: This study included 523 valid questionnaires. The mean knowledge and attitude scores were 13.20±6.20 (range: 0-26) and 43.68±6.01 (range: 21-50), respectively, indicating poor knowledge and favorable attitude. Multivariable logistic regression analysis showed that junior high school education (OR=2.160, P=0.035), high school or technical school education (OR=2.356, P=0.039), and monthly average income > 5000 RMB (OR=3.407, P=0.002) were independently associated with knowledge. Knowledge (OR=1.095, P=0.002), BMI ≥ 24.0 kg/m2 (OR=0.372, P=0.011), junior high school (OR=3.699, P=0.002), high school or technical school (OR=2.903, P=0.028), high associate degree or above education (OR=6.068, P=0.014), monthly average income 3000-5000 RMB (OR=0.296, P=0.005), monthly average income > 5000 RMB (OR=0.225, P=0.021), with hypertension (OR=0.333, P=0.003), blood tests every 2-3 weeks (OR=10.811, P=0.011), blood tests every month (OR=4.221, P=0.024), and blood tests every 2-3 months (OR=3.342, P=0.033) were independently associated with attitude. Conclusion: CAD patients who underwent coronary revascularization had poor knowledge but favorable attitudes toward postoperative antithrombotic management and prevention. The study underscores the need for targeted education, especially for individuals with lower education and income levels, ultimately improving patient compliance and cardiovascular outcomes. Keywords: Myocardial infarction; knowledge; attitude; antiplatelet drugs; cross-sectional study